(untitled) (Englisia : Journal of Language, Education, and Humanities, 2025)
This study investigates the integration of ecolinguistic principles into English language instruction for tourism students to enhance their environmental awareness and communication skills. Employing a qualitative approach, the research involved 29 tourism students at the Denpasar Academy of Tourism in Indonesia. Data were gathered through a practical adventure tour activity and individual interviews. The findings reveal that ecolinguistic strategies significantly improved students’ use of environment-related vocabulary, increased their confidence in discussing ecological issues in English, and cultivated a stronger sense of environmental responsibility. The study suggests that embedding ecolinguistics in English tourism education equips future professionals with the linguistic tools to promote sustainability in the tourism industry.